Application of Buffer Distance Standard for Industrial Lands: A Case Study of Phitsanulok Logistic Station - Judphol, Jirakrit (Journal of Architectural/Planning Research and Studies (JARS), 2022)
A buffer distance, widely used as a method of spatial management around an industrial area, is identified to reduce negative impacts from industrial production processes on the surrounding area. Logistic station is considered a service-oriented industry. Activities in a logistic station could generate negative impacts that include noise and air pollution, to wider areas. At present, there are various standards to draw buffer distances for manufacturing types. However, a specific standard for logistic stations has not been identified. This paper aims to propose buffer zone standards for logistic stations by reviewing existing buffer zones used in industrial areas. This research analyzes buffer distances through an examination of physical characteristics of industrial areas and activity areas related to a logistic station. The proposed standard can be defined based on two main factors: i) physical properties of logistic stations, and ii) activities in logistic stations. The Phitsanulok logistic station project, which is currently being considered and planned for construction in the future, is a case study to illustrate an application of the proposed buffer distance standards.